Vakwerkbouw in Nederlands Limburg en de raakvlakken met het Rijnland - Eggen, Coen (Rheinische Heimatpflege, 2020)
Keywords: Baustil; Fachwerkbau; Niederrhein-Gebiet; Südlimburg (Niederlande)

Hoop en wanhoop aan weerszijden van de grens = Hoffnung und Verzweiflung auf beiden Seiten der Grenze - Peeters, Els (Heemkundevereniging 'De Bongard' Simpelveld-Bocholtz, 2020)
Inhaltsverzeichnis: http://bvbr.bib-bvb.de:8991/exlibris/aleph/a24_1/apache_media/KX713AJ9PEXH87H7TU3NCLPC435KVS.pdf
Keywords: Grenzgebiet; Rheinland; Südlimburg (Niederlande); Zweiter Weltkrieg

Bevrijding Oostelijke Mijnstreek. Het Amerikaanse leger aan het werk rondom de bevrijding van Hoensbroek en omstreken - Heltzel, Hans (Stichting Historische Kring 'Het Land van Herle', 2019)
Keywords: Befreiung; Heerlen; Hoensbroek; Südlimburg (Niederlande); Westwall; Zweiter Weltkrieg

Alsof de taalgrens niet bestond. Limburgse kompels in de Luikse kolenmijnen na de Tweede Wereldoorlog - Rutten, Willibrord (Het Land van Herle. Historisch tijdschrift voor oostelijk Zuid-Limburg, 2009)
Keywords: Grenzarbeitnehmer; Lüttich; Sprachgrenze; Steinkohlenbergbau; Südlimburg (Niederlande)

Over de streep. Grensarbeid vanuit Zuid-Limburg naar Duitsland 1958–2001 - Bouwens, Sophie (Verloren, 2008)
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage/2009/02/14/file_18/2815985.pdf
Keywords: Grenzarbeitnehmer; Südlimburg (Niederlande)

Secondary labour force of permanent staff? Foreign workers in the Aachen coal mines - Klank, Kristin (TSEG - The Low Countries Journal of Social and Economic History, 2008)
Abstract: „The paper gives an overview of the recruitment and professional status of workers in the coal mining district of Aachen from different origins, i.e. local miners, miners from other German coal districts, cross-border commuters from Dutch South-Limburg and labour migrants. Migration history generally assumes that foreign workers were primarily employed as temporary workers in workplaces abandoned by the local population. This article argues that the labour market situation of foreign commuters and labour immigrants has to be studied separately. Commuters were primarily skilled miners, who came to the mines on their own account. After the First World War, labour mobility between the Aachen region and South-Limburg was ephemeral and often resulted from sudden institutional changes. In general, long distance labour migrants were unskilled. They arrived in the mines in large groups hired directly by agents of the mines or mediated by the Federal Employment Office. The position of foreign immigrants underwent important changes. During the first recruitment drives of the Aachen mines between 1906 and 1912, immigrants were indeed considered as temporary workers; after the Second World War, the companies tried hard to make these workers stay beyond the minimal period of one year. Long-term labour contracts could lead to integration of immigrant workers into the permanent workforce, but also penalised workers who wished to leave prematurely.“
Keywords: Aachen (Region); Arbeitsmigration; Niederländer; Steinkohlenbergbau; Südlimburg (Niederlande)

Regional labour markets and international migration in twentieth-century Europe. The cases of coal mining in Liège (B) and Limburg (NL) compared - Langeweg, Serge; Roels, Leen; Knotter, Ad (Mitteilungsblatt des Instituts für Soziale Bewegungen. Forschungen und Forschungsberichte, 2008)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau; Südlimburg (Niederlande)

Trekarbeiders en pendelaars. Grensarbeid in oostelijk Zuid-Limburg, 1875–1914 - Langeweg, Serge (Zestig jaar vorsen in de geschiedenis. Jubileumboek Het Land van Herle 1945–2005, 2006)
Keywords: Arbeitsmigration; Grenzarbeitnehmer; Südlimburg (Niederlande)

Werk in de marge? Grensarbeid vanuit het Nederlandse naar het Duitse deel van de Euregio Maas-Rijn, 1960–2000 - Bouwens, Sophie (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2005)
Keywords: Euregio Maas-Rhein; Grenzarbeitnehmer; Südlimburg (Niederlande)